Online market communicational patterns in developing countries: a Malaysian perspective - Shahid Bashir; Ridzuan Masri; Faridah Ibrahim; Vijayesvaran Arumugam (Universiti Kebangsaan Malaysian, 2014)
The aim of present study is to provide ideas across a variety of online buyer practices and choices that will assist communicators to be more set in market patterns of developing countries. The study signifies not just for the web-vendors in promoting online market, but also for those individuals who are hesitant to buy products online. On a sample size of 50 Malaysian e-shoppers, an open ended questionnaire was used as a primary data collection method to analyze buyer practicing ideas gathered around several variables reviewed through past studies i.e. web promotion, consumer’s decision making methodologies, extensive online clientage, and online shopping related knowledge. The outcomes evidenced powerful influence of some of these variables on online buyer’s practices.